Measles and Rubella: susceptibility in adolescents, young adults in Belém and Ananindeua, Pará, Brazil - Matos de Moraes, Marluce; Lobato da Silva, Dorotéa; Lopes Fernandes de Medeiros, Renato; Izabel de Jesus, Maria; do Espírito Santo Sagica, Fernanda (Seven Editora, 2023)
Measles and Rubella are infectious viral diseases, exanthematous, contagious, transmitted by the respiratory tract, similar clinical pictures that can evolve with severe complications. There is no specific treatment so far, both are of universal distribution, prevention is through vaccination. Objective: to evaluate the immune status in population aged 15 to 39 years as to measles and rubella, identifying susceptible between 2016 to 2018 in the municipalities of Belém and Ananindeua, Pará, Brazil. The detection of human IgG antibodies in blood serum were performed by the ELISA method. Considered susceptible individuals with non-reactive and inconclusive titers. In Belém, 1109 residents participated, the susceptible age groups for measles were 15 to 19 years (22.4%); 20 to 29 years (16.2%) and 30 to 39 years (8.8%). Ananindeua obtained 1111 participants, the age groups 15-19; 20-29; 30 to 39 years were vulnerable to measles virus, presenting susceptibility of 21%, 17.7% and 9.5% respectively, for rubella the age group 15 to 29 years was susceptible. There is a risk of measles and rubella outbreaks in the municipalities studied, pointing to the need to strengthen vaccination strategies, border monitoring, because the immigration of unvaccinated foreigners has contributed to the occurrence of measles outbreaks in Brazil in the last five years, causing the loss of certification of elimination of measles, and the threat of reintroduction of the rubella virus to Brazil. DOI: https://doi.org/10.56238/tfisdwv1-035